Influence of Shuttle Run and Zig-Zag Run Training on Crescent Kick Speed in Pencak Silat Athletes - Afran Wijaya; Nanang Indardi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to determine the effect of shuttle run and zig-zag run training on improving the speed of the crescent kick among pencak silat athletes at SMP Negeri 1 Bawang. Crescent kick speed enhances attack effectiveness in pencak silat. This study employs a quantitative approach using a quasi-experimental design with a pre-test post-test model. The study population consisted of all pencak silat athletes at SMP Negeri 1 Bawang who actively participated in train-ing activities. Total sampling was used (N=8), divided into two groups: the shuttle run training group and the zig-zag run training group. Data collection was con-ducted using a crescent kick speed test through pre-test and post-test admin-istrations. Data analysis was performed using normality tests, homogeneity tests, and the Independent Samples t-test with the assistance of SPSS software. The results showed a significance value of 0.003 (<0.05), indicating a significant dif-ference in the effects of shuttle run training and zig-zag run training on the cres-cent kick speed of pencak silat athletes. Shuttle run training was proven to yield higher improvements compared to zig-zag run training. Thus, shuttle run training is more effective for improving the crescent kick speed of student-aged pencak silat athletes.